1988
DOI: 10.1111/j.1151-2916.1988.tb05898.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Dissolution of Sapphire into Silicate Melts

Abstract: The forced-convective dissolution of sapphire into Ca0-Mg0-AI2O3-SiO2 melts was investigated at 1450" and 1550°C. Spinel, MgAI2O4, formed on the sapphire under all conditions although the morphology of the spinel, which varied from individual particles to a complete layer, depended on the MgO content of the melt, the rate of rotation of the specimens in the melt, and the temperature. The thermodynamic and kinetic conditions required for formation of spinel are considered, and the factors that are important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 13 publications
5
68
0
1
Order By: Relevance
“…After the same amount of time, but at 1500 °C, there is extensive spinel formation, but the layer is attached to the MgO at infrequent intervals. It is not clear whether the spinel has been undermined by slag penetration or, as proposed by Sandhage and Yurek, [14] it nucleates at the MgO refractory surface, and then grows sideways, trapping slag between the spinel and the MgO. At the higher temperature, more MgO dissolves before spinel precipitation occurs and the growth of spinel is faster.…”
Section: Effect Of Spinel Formation On the Rate Of Dissolution Of Mgomentioning
confidence: 81%
See 2 more Smart Citations
“…After the same amount of time, but at 1500 °C, there is extensive spinel formation, but the layer is attached to the MgO at infrequent intervals. It is not clear whether the spinel has been undermined by slag penetration or, as proposed by Sandhage and Yurek, [14] it nucleates at the MgO refractory surface, and then grows sideways, trapping slag between the spinel and the MgO. At the higher temperature, more MgO dissolves before spinel precipitation occurs and the growth of spinel is faster.…”
Section: Effect Of Spinel Formation On the Rate Of Dissolution Of Mgomentioning
confidence: 81%
“…[14,15,16] It is reasonable to expect that MgO refractory-slag systems where spinel forms during the dissolution of the refractory would have a different dissolution rate and rate constant from systems where no spinel forms. This is what other authors have argued, [14,15,16] who have shown that spinel slows the rate of refractory dissolution. What is most interesting about experiments at 1530 °C and 800 rpm for slag with alumina is that the overall rate is very similar to slag without alumina, indicating that any spinel formed does not provide significant protection to the MgO.…”
Section: Effect Of Spinel Formation On the Rate Of Dissolution Of Mgomentioning
confidence: 99%
See 1 more Smart Citation
“…refractories) in reports by Z. Yu et al 11) and K. Matsui et al 1) and the reaction between single-component materials and slag, for example, alumina ceramic refractories and steelmaking slag, represented by the report by K. Sandhage et al, 8,9) among others. However, there are few examples of reports on the reaction behaviour between practical fired refractories such as Al 2 O 3 -SiO 2 system bricks, which are used as safety bricks, and multi-component slags, as represented by steelmaking slag, in spite of the importance of this subject.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] To introduce some examples of research to date, the main objects of research were the reaction between steelmaking slag and MgO system refractories such as MgO-C brick ( (Received on October 4, 2016; accepted on December 6, 2016) The corrosion rate of Al 2 O 3 -SiO 2 system bricks, which are practical fired bricks, into CaO-SiO 2 -Al 2 O 3 -MgO slag was investigated, and the effects of temperature, refractory composition and mass transfer rate in slag on the corrosion rate of the bricks were discussed. As a result, the corrosion rate decreased as the alumina content in the brick increased.…”
Section: Introductionmentioning
confidence: 99%